Cry me a river: the environmental transformation of the Tarim River Basin and its impact on Chinese-Uyghur relations, 1949-2009 - Wang, Xiaoran, author; Didier, John, advisor; Fiege, Mark, committee member; Fisher, Christopher, committee member (Colorado State University. Libraries, 2011)
This thesis focuses in the study of the environmental, social, political, and economic / resource-extraction history of China's Xinjiang Province. Not only does the author trace the historically most significant environmentally depredating human events in Xinjiang over the past two thousand years, I also explains these events within the context of social, political, economic, and resource-extraction history, thus providing insight into the nature of the political, social, economic, and natural-resource backdrops that created the need of the Chinese to engage in environmentally hazardous / destructive activities in its far western / northwestern borderlands. My treatment in Section Two of the role that the Chinese government saw Xinjiang playing in the development of the Chinese economy and national security on the world stage enables not only China specialists but also non-specialists to grasp the overall impetus of the Chinese economic / security developments of the past 60 years.
Keywords: China; cotton; Tarim River; Uyghur; Xinjiang; XPCC